STUDI KASUS: KONSUMSI KACANG HIJAU UNTUK MENINGKATKAN KADAR HEMOGLOBIN IBU POSTPARTUM DENGAN ANEMIA BERAT - Jakob L. Jambormias; Kristiova Masnita Saragih (Jurnal Kebidanan, 2022)
Anemia in postpartum mothers is one that can lead to complications if not treated. In addition to iron tablets, green beans also play a role in the formation of red blood cells and have many ingredients that can help increase hemoglobin levels in postpartum mothers. This case study describes Mrs. S.M 23 years old, multiparity with Hb level 4.6 g%. The postpartum mother who experienced severe anemia consumed mung beans and combination of iron tablets and vitamin C. Observations of severe anemia in multiparity mothers were carried out through interviews, physical examination observations, literature studies and documentation. After consuming mung beans for 14 consecutive days carried out regularly 3 times a day, the mother said she felt more fresh, not weak, her Hb level increased to 6.2 g%. mother is happy with the situation. Based on the results above, it is concluded that the consumption of green beans can increase the Hb level in postpartum mothers by giving it in combination with the administration of iron tablets and Vitamin C.